2022
DOI: 10.1093/eurheartj/ehac544.669
|View full text |Cite
|
Sign up to set email alerts
|

Arrhythmia detection using insertable cardiac monitors after a negative electrophysiology study in Brugada syndrome: observations from a multicenter Spanish registry

Abstract: Background/Introduction Risk stratification in Brugada syndrome (BrS) remains controversial. In this respect, the role of electrophysiology study (EPS) has been subject of debate. It is common practice in some centers to implant an insertable cardiac monitor (ICM) after a negative EPS, especially in the presence of unexplained symptoms. However, the diagnostic value of this approach has never been specifically addressed. Purpose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The use of implantable cardiac monitors (ICMs) has been suggested as a potential strategy to mitigate the risk of SCD in BrS patients 3 . Recent observational studies have shown that cardiac arrhythmias, primarily atrial and brady arrhythmias, can often be detected and treated with this approach 4–6 . Nevertheless, the adoption of ICMs in BrS remains controversial, as even though these patients have a low risk of VA, cardiac arrest may manifest as the initial symptom.…”
Section: Introductionmentioning
confidence: 99%
“…The use of implantable cardiac monitors (ICMs) has been suggested as a potential strategy to mitigate the risk of SCD in BrS patients 3 . Recent observational studies have shown that cardiac arrhythmias, primarily atrial and brady arrhythmias, can often be detected and treated with this approach 4–6 . Nevertheless, the adoption of ICMs in BrS remains controversial, as even though these patients have a low risk of VA, cardiac arrest may manifest as the initial symptom.…”
Section: Introductionmentioning
confidence: 99%